Exploration of students' reaction in medical error events and the impact of personalized training on the speaking-up behavior in medical error events. (3rd April 2023) - Chen, Yi-Chun; Issenberg, S. Barry; Chiu, Yu-Jui; Chen, Hui-Wen; Issenberg, Zachary; Kang, Yi-No; Lin, Che-Wei; Wu, Jen-Chieh
Abstract: Background: The ability of medical students to speak up before a medical error occurs is a timely and necessary interaction to prevent potential patient harm. As it may be crucial to improve patient safety, we explored how medical students react to a medical error and provided them appropriate training regarding speaking up about medical issues. Methods: A quasi-experimental study was conducted in Taiwan involving 153 medical students who participated in a speaking-up simulation course. They were divided into two groups. The first group participated in a non-life-threatening scenario before the intervention, followed by a personalized debriefing session, then a life-threatening scenario after the intervention. The second group participated in a life-threatening scenario before the intervention, followed by a personalized debriefing session, then a non-life-threatening scenario after the intervention. Students also completed patient safety attitude survey. Results: During the preintervention scenario, the overall medical students' speaking-up rate to medical error was 45.1%. The speaking-up rate of medical students in life-threatening scenario was significantly higher than the rate in non-life-threatening scenario before the intervention (64.6% vs 24.3%, p  < 0.001). After personalized debriefing, the speaking-up rate to medical errors was significantly improved both in life-threatening scenarios (95.9%, p  < 0.001) and in non-life-threatening scenarios (100%, p <  0.001). Male medical students had significantly higher speaking-up rates than female students in life-threatening scenario (76.2% vs 51.4%, p  = 0.02). On post-intervention surveys, students provided several reasons for their likelihood of speaking up or remaining silent during a medical error event. Conclusions: Medical students' rate of speaking-up to medical error was higher in a simulated life-threatening scenario than in a simulated non-life-threatening scenario. Faculty-led personalized debriefing can facilitate medical students' adoption of communication strategies to speak up more in medical error events. Educators should also consider gender differences when they design effective assertive communication courses.